ANALISIS PRODUKSI KULTURAL PIERRE BOURDIEU DALAM NASKAH-NASKAH TEATER ANDHI SETYO WIBOWO - Mokhammad Farosya Asy'ari; Agus Sulton (Kajian Linguistik dan Sastra, 2023)
Abstract This study aims to analyze ‘practice’ in the form of Andhi Setyo Wibowo’s theatrical scripts in Pierre Bourdieu’s Theory of Cultural Production. This study uses a critical descriptive paradigm, the researcher focuses on the analysis of sources and data received by utilizing the theory used, namely Pierre Bourdieu’s theory of cultural production. There are three problem formulations that will be explained by the researcher. First, the context that shapes Andhi Setyo Wibowo’s habitus in producing his works. Second, how does Andhi Setyo Wibowo manage his modalities. Third, how Andhi Setyo Wibowo represented his theatrical scripts in the theater arena in East Java. Abstrak Penelitian ini memiliki tujuan untuk menganalisis ‘prakti’ berupa naskah-naskah teater Andhi Setyo Wibowo dalam Teori Produksi Kultural Pierre Bourdieu. Penelitian ini menggunakan paradigma deskriptif kritis, peneliti menitikberatkan pada analisis sumber dan data yang diterima dengan memanfaatkan teori yang digunakan yakni teori produksi kultural Pierre Bourdieu. Terdapat tiga rumusan masalah yang akan dijelaskan peneliti. Pertama, konteks yang membentuk habitus Andhi Setyo Wibowo dalam memproduksi karyanya. Kedua, bagaimana cara Andhi Setyo Wibowo mengelola modalitasnya. Ketiga, bagaimana cara Andhi Setyo Wibowo merepresentasikan naskah-naskah teaternya dalam arena teater di Jawa Timur.